The Genus Spilanthes Ethnopharmacology, Phytochemistry, and Pharmacological Properties: A Review - Jayaraj Paulraj; Raghavan Govindarajan; Pushpangadan Palpu (Advances in Pharmacological Sciences)
Spilanthes spp. are popular, over-the-counter remedies; they are sold over the internet under various names and are widely used in traditional medicine in various cultures. This review will summarize the important reports on the ethnopharmacology, botany, phytochemistry, and pharmacological properties as described in the literature from recent years (1920 to 2013). Spilanthes spp. are used for more than 60 types of disorders. They are reported to contain a number of biologically active phytochemicals, although a large number of ethnopharmacological uses have been documented; only a few of these species have been investigated for their chemical and biological activities. The studies are carried out mainly on Spilanthes extracts and a few metabolites substantiate the uses of these plants in traditional medicine. Well-conducted pharmacological studies are still needed for several traditional indications, and the mechanisms of action by which the plant extracts and the active compounds exert their pharmacological effects remain to be studied. They are predominantly used as extracts in personal care products, traditional medicines, and the pharmaceutical and culinary areas. Suggestions are made regarding some of the possible mechanisms of action as to how the known compounds may exert their biological activity.